Anticancer potential of mebendazole against chronic myeloid leukemia: in silico and in vitro studies revealed new insights about the mechanism of action - Daniel, Julio Paulino; Mesquita, Felipe Pantoja; Da Silva, Emerson Lucena; de Souza, Pedro Filho Noronha; Lima, Luina Benevides; de Oliveira, Lais Lacerda Brasil; de Moraes, Maria Elisabete Amaral; Moreira-Nunes, Caroline de Fátima Aquino; Burbano, Rommel Mario Rodríguez; Zanatta, Geancarlo; Montenegro, Raquel Carvalho (Frontiers in Pharmacology, 2022)
Chronic myeloid leukemia (CML) is caused by the constitutively active fusion protein BCR-ABL1 and targeting ABL1 is a promising therapy option. Imatinib, Dasatinib, and Nilotinib have all been shown to work effectively in clinical trials. ABL1 mutations, particularly the T315I gate-keeper mutation, cause resistance in patients. As a result, broad-spectrum ABL1 medicines are desperately needed. In order to screen potential drugs targeting CML, Mebendazole (MBZ) were subjected to in vitro test against CML cell lines (K562 and FEPS) and computational assays. The antiproliferative effect of MBZ and their combination with tyrosine kinase inhibitors (TKIs) was tested using end-point viability assays, cell cycle distribution analysis, cell membrane and mitochondrial dyes. By interrupting the cell cycle and causing cell death, MBZ and its combination with imatinib and Dasatinib have a significant antiproliferative effect. We identified MBZ as a promising "new use" drug targeting wild-type and mutant ABL1 using molecular docking. Meanwhile, we determined which residues in the allosteric site are important in ABL1 drug development. These findings may not only serve as a model for repositioning current authorized medications, but they may also provide ABL1-targeted anti-CML treatments a fresh lease of life.